Atezolizumab for the treatment of renal cell carcinoma. (2nd July 2020) - Lafon, Mathilde; Domblides, Charlotte; Daste, Amaury; Sionneau, Baptiste; Ravaud, Alain; Bernhard, Jean-Christophe; Gross-Goupil, Marine
ABSTRACT: Introduction: The therapeutic landscape of renal cell cancer has evolved rapidly over the past 2 years with nivolumab and ipilimumab for patients with metastatic disease and an intermediate or poor prognosis, in the first line setting. More recently, data from trials combining antiangiogenic agents and immune checkpoint inhibitors demonstrated a major benefit of this treatment approach for all patients. Areas covered: One of three recent trials evaluated the combination of atezolizumab, an anti-programmed death ligand 1 antibody, with bevacizumab, an anti-vascular endothelial growth factor monoclonal antibody. In this manuscript, we summarize the preclinical, clinical, and safety data on atezolizumab for treatment of renal cell carcinoma and describe ongoing trials. Expert opinion: Atezolizumab was evaluated in combination with an antiangiogenic agent. These trials were designed based on the hypothesis that selecting patients according to the expression of programmed death ligand 1 would increase the benefit of the treatment combination. Despite positive effects on the primary endpoints progression-free survival and response rate in this selected population, overall survival in the global population did not meet the criteria for significance at the time of the intermediate analysis. The major information was a proposed tumor gene expression signature. The signature was predictive of the sensitivity to anti-angiogenic and/or immune checkpoint inhibitor therapy.